Indonesian Language Pride in Multicultural Indonesian-Korean Family: A Sociolinguistic Study of The Kimbab Family Youtube Chanel - Alemina Br. Perangin-angin; Maghfirah Rit Atusaadah; Vivi Adryani Nasution (TALENTA Publisher, 2024)
The research was conducted to demonstrate Indonesian language pride on the Kimbab Family YouTube channel. The purpose of this study is to examine how an Indonesian-Korean multicultural family uses Indonesian in regular discourse on YouTube. To promote Indonesia as the nation's identity overseas, advanced technologies must be utilized. YouTube is one of these numerous virtual platforms that attract users from all around the world. This situation encourages Indonesian to compete with other languages; therefore, efforts to promote and preserve Indonesian must be supported. The data for this descriptive qualitative study was collected through documentation and listening. The data were YouTube comments from the Kimbab Family channel. According to the results of this study, the Kimbab family is proud of their Indonesian language skills. The Indonesian employed on the YouTube channel of Kimbab Family may be categorized into eight categories: questioning, replying, explaining/informing, inviting, demanding, quizzing, promoting, and joking.